Asymptomatic Bacteriuria amongst Menopausal women in Calabar, Nigeria - Inyang-Etoh, Paul Columba; Akpan, Abasiodiong Udom; Usanga, Victor Udo; Ejezie, Gabriel Chuks (Asian Journal of Medical Sciences, 2018)
Background: Bacteriuria is considered a common bacterial infection in women particularly in postmenopausal women which consequently may warrant the need to treat the disease for prevention of bacteriuria developing complications. Aims and Objectives: This work was to investigate the prevalence of asymptomatic bacteriuria among menopausal women in Calabar, the incriminating bacterial pathogens and their antibiotic susceptibility pattern. Materials and Methods: Early morning mid stream urine samples from randomly selected 200 women (comprising of 50 premenopausal, 50 menopausal, 50 postmenopausal women and 50 apparently healthy young ladies of menstruating age (control subjects)) between the ages of 50 to 90 years were cultured by Leigh and Williams’s method. Questionnaires were also administered. Results: 24 (16%) of the test group while 3 (6%) of the control group had infection (p=0.008). Subjects aged 35-40 years had the highest prevalence of infection 6 (18.5%), while age group 66-70yrs had the lowest infection rate 0(0%)( P = 0.841). Post-menopausal women had the highest prevalence of asymptomatic bacteriuria 10(20%) while pre-menopausal and menopausal women had a lower prevalence rate of 7 (14%) each (p=0.0687). The most frequently isolated organism was Staphylococcus aureus (33%) and Ciprofloxacin was the most sensitive antibiotic observed. Conclusion: This work has revealed a high prevalence rate of asymptomatic bacteriuria high level of asymptomatic bacteriuria among menopausal women and the need for routine screening of this category of women for a standard healthy living. Asian Journal of Medical Sciences Vol.9(4) 2018 51-56